Synthesis and Characterization of New 1,3,4-Oxadiazole Derivatives from Sulfathiazole - Jassim Jassim; Aws Nejres; Laith Atiyah; Hussein Ibrahim; Zeyad Hameed (University of Mosul, 2024)
Background: Oxadiazole are important heterocyclic compounds in organic chemistry. Methods: In this work, a series of new 1,3,4-oxadiazole moiety started from diazonium salt was synthesized. The latter (A1) was prepared form sulfathiazole compound by reacting it with sodium nitrite in an acidic medium. This was followed by its conversion to azide derivative through the reaction with sodium azide, resulting in the compound azide sulfathiazole (A2). The latter was utilized as a good starting material for the preparation of 1,2,3-triazole-4-carboxylic acid derivative (A3). The carboxylic acid moiety of which was converted to an ester derivative (A4) by reacting it with absolute ethanol in a concentrated sulfuric acid medium. The ester derivative was subsequently reacted with hydrazine hydrate to yield the hydrazide derivative (A5), which serves as the starting material for the preparation of oxadiazole compounds. The hydrazide (A5) reacts with the substituents benzoic acid under dry condition in the presence of POCl3 to obtain the compounds 1,3,4-oxadiazole derivatives (A6-A12). Conclusion: The target compounds were obtained and confirmed by conducting an analytical study using FT-IR spectrophotometer.